Diskursus Pilkada Jawa Timur 2018 Di Media Televisi Lokal TV9 - Setianingrum, Vinda Maya; Huda, Anam Miftakhul; Indrajayani, Galuh Gita (Universitas Merdeka Madiun, 2020)
Abstractâ€” General election to be one of public concern because in the process leaders will be selected both at the executive and legislative levels. Television media makes the implementation of elections as the content of choice to be broadcast to the public. If the national election is packaged in a broadcast program on national television, then the holding of regional head elections or local elections becomes the material for broadcast programs on local television. East Java is the province that held simultaneous regional elections in 2018, both the election of the Governor and the election of Regents and Mayors. This moment was then managed by TV9, which was one of the local televisions in East Java to present a dialogue program called Ruang Pilkada. From this background, the researcher wanted to find out how the results of the discussion presented in the broadcast program were related to the East Java elections. Talks from the speakers were important to describe as references to the next election. This study uses a case study method and collects data through interviews, observation, and documentation. The result is that the regional election broadcast program can provide an overview of the implementation of the election in accordance with the expected stages and processes of democracy. The discourse in the broadcast program is a reference that the socialization and discussion that educates the public will have an impact on the implementation of a safe and dignified local election.Â Keywordsâ€”: broadcast media; television program; East Java regional election;TV9.